Evaluation of the microbial diversity and heavy metal resistance genes of a microbial community on contaminated environment - Xavier, J.C.; Costa, P.E.S.; Hissa, D.C.; Melo, V.M.M.; Falcão, R.M.; Balbino, V.Q.; Mendonça, L.A.R.; Lima, M.G.S.; Coutinho, H.D.M.; Verde, L.C.L. (Applied geochemistry, 2019)
Heavy metals are low molecular weight elements which at certain concentrations can cause environmental problems as they accumulate. These metals can be toxic depending on their concentration despite being essential to the metabolism of most organisms. Their accumulation in the environment is mainly due to anthropogenic actions which are difficult to revert. In this context, bacteria have been used to efficiently bioremediate the environment. The aim of this study was to map heavy metal resistant genes from bacterial communities in the Riacho dos Macacos compared to those from Rio Grangeiro, used as the environmental control due to its low heavy metal concentration. The samples were prepared by removing the soil and taking these to a laboratory for DNA extraction and subsequent sequencing using the Illumina Miseq kit. Physico-chemical analysis was also performed to quantify the heavy metal concentration in samples. The data were input in the MG-RAST and analyzed. Various genes associated with copper resistance such as Cu ATPase, multicopper oxidase, czc as well as genes associated with zinc resistance were found, especially from the czc family. In the resistant gene taxonomic analysis, the most common bacterial phyla were Proteobacteria with 49.96% and 59.29%, and Actinobacteria with 23.55 and 12.06% in Riacho dos Macacos and Rio Grangeiro, respectively. Other phyla totaled only 27.63% and 32.12%, respectively. •The Anaeromixobacter and Geobacter were the most abundant genera with zinc resistant genes.•The Pseudomonas and Nocardioides demonstrated an abundance of copper resistant genes.•The most abundant genes belonged to the czcD family, involved in zinc resistance.•The P-type ATPase or CopA The most abundant genes against copper.